2012
DOI: 10.1016/j.neuroimage.2011.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric bias in user guided segmentations of brain structures

Abstract: Brain morphometric studies often incorporate comparative hemispheric asymmetry analyses of segmented brain structures. In this work, we present evidence that common user guided structural segmentation techniques exhibit strong left-right asymmetric biases and thus fundamentally influence any left-right asymmetry analyses. In this study, MRI scans from ten pediatric subjects were employed for studying segmentations of amygdala, globus pallidus, putamen, caudate, and lateral ventricle. Additionally, two pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…While prior PiB studies in MCI and AD have not conclusively shown hemispheric asymmetry in amyloid deposition [44], PiB signal in the left, but not right, hemisphere in AD patients correlates with both cognitive performance and regional hypometabolism on FDG PET [45]. Alternatively, it has also been suggested that manual hippocampal volumetric analyses may be subject to asymmetric left-right biases [46]. This phenomenon could have theoretically impacted our results, even though our hippocampal indices were derived from automated segmentation, since the initial training set was developed through manual tracing.…”
Section: Discussionmentioning
confidence: 99%
“…While prior PiB studies in MCI and AD have not conclusively shown hemispheric asymmetry in amyloid deposition [44], PiB signal in the left, but not right, hemisphere in AD patients correlates with both cognitive performance and regional hypometabolism on FDG PET [45]. Alternatively, it has also been suggested that manual hippocampal volumetric analyses may be subject to asymmetric left-right biases [46]. This phenomenon could have theoretically impacted our results, even though our hippocampal indices were derived from automated segmentation, since the initial training set was developed through manual tracing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study controlled for medication use, alcohol use, education, and other variables that might influence the relationship between depression and hippocampal volume. Another potential strength is the use of an automated method to derive hippocampal volumes that results in excellent reproducibility (Lucarelli et al, 2012;Nugent et al, 2012) and avoids a left-right bias that may be inherent with manual segmentation (Maltbie et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed "laterality of visual perception" as an inherent limitation in any study using user interaction in hippocampal segmentation and further suggested a reappraisal of prior work in light of this finding. 1 Thus, data previously reported by using manual segmentation have the potential for material bias.…”
Section: Discussionmentioning
confidence: 99%
“…1 At present, to our knowledge, there are no large studies with broad ethnic representation using high-resolution MR imaging, with consistent application of automated measures of the hippocampus to define the range of values of hippocampal asymmetry in the general population.…”
mentioning
confidence: 99%